2018
DOI: 10.1111/eip.12763
|View full text |Cite
|
Sign up to set email alerts
|

Exploratory comparison of auditory verbal hallucinations and other psychotic symptoms among youth with borderline personality disorder or schizophrenia spectrum disorder

Abstract: Objective: This study explored phenomenological aspects of auditory verbal hallucinations (AVH) and other psychotic symptoms among youth with borderline personality disorder (BPD).Methods: Sixty-eight outpatients, aged 15 to 25 years, were categorized into three groups according to their primary Diagnostic and Statistical Manual of Mental Disorders, Fifth Edition (DSM-5) diagnosis and AVH symptom profile; BPD + AVH (n = 23), schizophrenia spectrum disorder (SZ) + AVH (n = 22) and BPD with no AVH (n = 23).Resul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
34
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 21 publications
(38 citation statements)
references
References 53 publications
3
34
0
Order By: Relevance
“…Following a transdiagnostic approach toward understanding and treating distressing voices, we recently explored AVH in a sample of outpatient youths with BPD compared with those with a schizophrenia spectrum disorder (SZ). The main findings that emerged from the study are that: (1) AVH in youths with BPD are phenomenologically indistinguishable from those in SZ [28] and (2) both negative appraisals of voices and negative voice content predicted more severe depression, regardless of the diagnosis (BPD vs. SZ), while AVH severity (i.e., frequency, duration, location, and loudness) was not correlated with depression [29]. Using the same sample [28,29], the aim of the current study was to better understand the role of interpersonal schemata within the relationship between appraisals of voices and depression in young voice hearers, whose identity is still developing.…”
Section: Introductionmentioning
confidence: 89%
See 1 more Smart Citation
“…Following a transdiagnostic approach toward understanding and treating distressing voices, we recently explored AVH in a sample of outpatient youths with BPD compared with those with a schizophrenia spectrum disorder (SZ). The main findings that emerged from the study are that: (1) AVH in youths with BPD are phenomenologically indistinguishable from those in SZ [28] and (2) both negative appraisals of voices and negative voice content predicted more severe depression, regardless of the diagnosis (BPD vs. SZ), while AVH severity (i.e., frequency, duration, location, and loudness) was not correlated with depression [29]. Using the same sample [28,29], the aim of the current study was to better understand the role of interpersonal schemata within the relationship between appraisals of voices and depression in young voice hearers, whose identity is still developing.…”
Section: Introductionmentioning
confidence: 89%
“…All of the participants were fluent in English. The sample is the same as reported in Cavelti et al [28,29]. Two participants did not complete the questionnaires and were excluded from the analyses reported here.…”
Section: Participantsmentioning
confidence: 99%
“…Forty-three help-seeking youth, aged 15–25 years, with AVH, who were diagnosed with either BPD (BPD+AVH; n = 23) or schizophrenia spectrum disorder (SZ) (SZ+AVH, n = 20) according to the Diagnostic and Statistical Manual of Mental Disorders , 5th Edition (DSM-5) (31) and were fluent in English, participated in the study. They constituted a subsample of a study that has been reported elsewhere (30). Two participants from the original SZ+AVH group ( n = 22) did not complete the questionnaires, and were thus excluded from these analyses.…”
Section: Methodsmentioning
confidence: 99%
“…In order to examine whether beliefs, emotions, and behaviors associated with AVH in youth with BPD differed from those in youth with SZ and AVH (exploratory aim 1 and Hypothesis 1), group comparisons were performed using the Mann–Whitney U test for the BAVQ-R subscales and the DASS-21 subscales, as well as the t -test for independent samples for the VRS. Group comparisons of the PSYRATS-AH items have been reported elsewhere (30).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation